2010
DOI: 10.1007/s12206-010-0207-9
|View full text |Cite
|
Sign up to set email alerts
|

PIV study of vortexing during draining from square tanks

Abstract: The flow field in square tanks with various corner roundings is studied to investigate drain flow characteristics. An attempt is made to understand the mechanism of flow field responsible for vortex suppression by the different radius of rounding at the corner. For this purpose, flow visualization studies using particle image velocimetry are employed to determine the flow patterns in a square tank. Results are obtained for no draining and with draining experiments. The flow field is visualized both in horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…10 He suggested that interaction of draining liquid with sharp corners has led to the vortex suppression in square and rectangular tanks. Results of PIV studies of Sohn et al 11 also comply with the findings of Gowda. 10 Nazir and Sohn 12,13 revealed in their study that axial and swirl velocities can significantly influence the phenomenon of air core vortexing.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…10 He suggested that interaction of draining liquid with sharp corners has led to the vortex suppression in square and rectangular tanks. Results of PIV studies of Sohn et al 11 also comply with the findings of Gowda. 10 Nazir and Sohn 12,13 revealed in their study that axial and swirl velocities can significantly influence the phenomenon of air core vortexing.…”
Section: Introductionsupporting
confidence: 80%
“…As density of air r air is much less than density of water r, the term in equation ( 10) can be neglected. The resulting equation is given by equation ( 11), from which one can infer that pressure inside the forced vortex is not a function of radial distance r. This follows that the pressure at the center of the drain port P has the same value as the pressure at r = R max as revealed in equation (11). It should be noted that, in equations ( 10) and ( 11), P N is defined as the pressure at an infinite radial location from the center of the cylinder.…”
Section: Resultsmentioning
confidence: 96%
“…This liquid height is the critical height. By inserting r cr , as obtained by (5), into (4) and considering that at the critical height P r = P gas , the critical height is obtained as:…”
Section: Theoretical Approach For Predicting the Critical Heightmentioning
confidence: 99%
“…Ramamurthi and Tharakan [3] studied the effectiveness of shaped ports in suppressing air vortex and they found that a stepped drain port is effective to prevent vortex formation. Sohn et al [4] used the tanks of square cross-section for suppressing the vortex formation. Lakshmana Gowda et al [2] have suggested the dish-type (or cu-shaped) suppressor to prevent vortex formation during draining after imparting initial rotation.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that base inclination as well as position of drain ports eccentric to the tank axis can reduce the critical height. Sohn et al 9,22 analyzed the influence of eccentric drain holes and square cross-section tanks on vortex motion through experiments with rotating tanks. Adopting Particle Image Velocimetry (PIV) technique for flow visualization, they concluded that (a) tank rotation speed did not influence critical height above 90 rpm and (b) eccentric drain ports as well as square tanks reduce the intensity of vortexing phenomenon.…”
Section: Introductionmentioning
confidence: 99%